Post-Soviet Power State-Led Development and Russia's Marketization - Wengle, Susanne A. (Academic Studies Press, 2022)
Post-Soviet Power tells the story of the Russian electricity system and examines the politics of its transformation from a ministry to a market. Susanne A. Wengle shifts our focus away from what has been at the center of post-Soviet political economy - corruption and the lack of structural reforms - to draw attention to political struggles to establish a state with the ability to govern the economy. She highlights the importance of hands-on economic planning by authorities - post-Soviet developmentalism - and details the market mechanisms that have been created. This book argues that these observations urge us to think of economies and political authority as mutually constitutive, in Russia and beyond. Whereas political science often thinks of market arrangements resulting from political institutions, Russia's marketization demonstrates that political status is also produced by the market arrangements that actors create. Taking this reflexivity seriously suggests a view of economies and markets as constructed and contingent entities.